Linguistic Application Using Transitivity-Appraisal Analysis - Alexander Setiawan; Djoni Haryadi Setiabudi; Yanuar Simon (Institute of Advanced Engineering and Science, 2011)
AbstractIn conducting research and linguistic analysis, researchers often find a variety of obstacles because of their limitations as human beings. A large number of articles data that must be processed and calculated increase the risk of error in the analysis, either in error in classification or error in the calculation. That’s why an application is made to assist researchers in conducting their research. This research was provided a specific framework to support the needs analysis process. This program is specifically designed to support the entire process of analysis required by using the method of analysis transivity analysis and assessment, which include searching and data processing articles, clauses classification process, and analytical assessment of this clause. The results of this study are to perform data storage process of said search results of an article, save the data analysis process from an article, the classification of phrase in the sentence in the article, and can minimize risk of calculation errors that occur in analysis. Test carried out using aplha reliability coeficient 0,75 (75%). Keywords: Analyze, Linguistic, Application.DOI:http://dx.doi.org/10.11591/ijece.v1i2.11